Stock markets : a spur to economic growth. - LEVINE, Ross (1996)
Notes that stock markets affect economic activity through the creation of liquidity. Greater stock market liquidity in developing countries is linked to a rise in the amount of capital raised through bonds and bank loans. Suggests that policy makers should consider reducing impediments to stock market development, and a good place to start would be by easing restrictions on international capital flows.